Alcohol Use and Misuse Among Chinese Psychiatrists During the Early COVID-19 Pandemic - Mo, Daming; Min, Kaiyuan; Gluck, Rachel; Jiang, Feng; Tao, Rui; Geng, Feng; Xia, Lei; Liu, Tingfang; Liu, Yuanli; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Psychiatry, 2022)
Aim: Survey alcohol use and misuse among Chinese psychiatrists during the Coronavirus diseases 2019 (COVID-19) pandemic. Methods: We conducted a large-scale, nationwide online survey of psychiatrists regarding their alcohol use during the pandemic. The Alcohol Use Disorder Identification Test-Concise (AUDIT-C) was used to assess alcohol use and misuse. Results: Of 3815 psychiatrists who completed the survey. Alcohol use and misuse rates were 47.5% and 8.2% respectively, and both were significantly higher in males. The majority (59%) reported no change in alcohol use during the pandemic, one-third (34.5) reported a decrease, and 6.5% reported an increase. Alcohol misuse was associated with middle-age (OR=1.418), male sex (OR = 5.089), Northeast China (OR =1.507), cigarette-smoking (OR =2.335), insomnia (OR =1.660), and regular exercise (OR =1.488). Master's degree (OR=0.714) and confidence in clinical work (OR =0.610) were associated with less alcohol misuse. Those who reported a decrease in alcohol use during the pandemic were more likely to be male (OR = 2.011), located in Northeast China (OR =1.994), and feel confident in their clinical work (OR =1.624). Increased alcohol use was significantly associated with insomnia (OR =3.139). Conclusions: During the COVID-19 pandemic, alcohol use and misuse among Chinese psychiatrists declined. While males were more likely to misuse alcohol, they were also more likely to have reduced their intake. Age, location, and lifestyle factors also predicted alcohol use and misuse. Further examination of specific factors that reduced alcohol use and misuse may help guide public health efforts to sustain the lower rates beyond the pandemic.